2011
DOI: 10.1590/s0037-86822011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiology among the elderly presenting acute respiratory infection during the influenza season

Abstract: Introduction: Acute respiratory tract infections are the most common illness in all individuals. Rhinoviruses have been reported as the etiology of more than 50% of respiratory tract infections worldwide. The study prospectively evaluated 47 elderly individuals from a group of 384 randomly assigned for acute respiratory viral infections (cold or flu) and assessed the occurrence of human rhinovirus (HRV), influenza A and B, respiratory syncytial virus and metapneumovirus (hMPV) in Botucatu, State of São Paulo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The outpatients had upper respiratory tract infections with flu-like symptoms and all hospitalized children had lower respiratory tract infections 19 . Other studies have shown a significant positivity for HMPV in Brazil as well 7,8,16,20,38,40,51,59,60 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The outpatients had upper respiratory tract infections with flu-like symptoms and all hospitalized children had lower respiratory tract infections 19 . Other studies have shown a significant positivity for HMPV in Brazil as well 7,8,16,20,38,40,51,59,60 .…”
Section: Discussionmentioning
confidence: 81%
“…In Brazil, epidemiological studies have demonstrated the importance of viruses as etiological agents of respiratory disease 5,7,8,10,14,16,17,19,25,29,33,35,38,40,43,51,53,59,60 . However, because such studies are mostly focused on the most common respiratory pathogens (FLUAV, HRSV, HPIV, HRV and HAdV), the role of emerging viruses as etiological agents of respiratory disease among Brazilian children remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of respiratory viral infections (RVIs) in immunocompetent adults is often overlooked; however, available data suggest that RVIs are responsible for a significant number of respiratory infections affecting not only the elderly (persons aged ≥65 years) but also young adults. 12,13,[27][28][29][30][31][32] Although the majority of infections in young adults are not life-threatening they can impose a significant burden on communities since the affected population represents a large fraction of the work force in developing countries. Data presented in this report indicate that 65.1% (28/43) of virus-positive samples were detected in patients <60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…8,33 HRV and HMPV were detected in 28.6% and 2%, respectively, in elderly patients. 29 Even so, a study performed in Porto Alegre (Southern Brazil) between November 2008 and October 2010 reported that 22% of infections in immunocompetent adult patients (median age 50.6 years of age) admitted to emergence rooms with ILI or severe acute respiratory infection (SARI) were caused by respiratory viruses, mostly FLUAV and HRV-A/B. FLUVB, HAdV, HPIV, HRSV, HMPV, and HCoV were less frequently detected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in other populations that multiple respiratory viruses such as parainfluenza virus, rhinovirus, adenovirus, metapneumovirus, respiratory syncytial virus (RSV), and coronavirus can cause ILI, 4 but the virologic etiology varies greatly among geographic locales, age groups, seasons, and years. [5][6][7][8][9][10][11][12][13] Some studies have suggested that specific symptoms could be used for the clinical prediction of the etiology of ILI, [14][15][16][17][18] though most of these studies only compared influenza to noninfluenza etiology.…”
Section: Introductionmentioning
confidence: 99%